2014
DOI: 10.1021/jp508979u
|View full text |Cite
|
Sign up to set email alerts
|

Role of Hydrogen Abstraction Acetylene Addition Mechanisms in the Formation of Chlorinated Naphthalenes. 1. A Quantum Chemical Investigation

Abstract: The addition of chloroacetylene or tetrachlorovinylacetylene to 2,4,5-trichlorophenyl radicals, leading to the formation of tetra-, penta-, and hexachloronaphthalene congeners, has been explored at the M06-2X/6-311+G(3df,3p)//B3LYP/6-31G(d) level of theory. The accuracy of this method was justified by comparing the barriers of several pertinent reactions against energies from single point calculations at the B3LYP/cc-pVDZ, CCSD(T)/6-31G(d), and G2MS levels. Bittner-Howard and Frenklach hydrogen abstraction ace… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
37
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(41 citation statements)
references
References 60 publications
4
37
0
Order By: Relevance
“…The chlorinated 2-vinylphenyl radicals to which the second acetylene adds are typically found to be higher in energy than the 2-phenylvinyl radicals which serve as the base in Bittner−Howard routes, but far less susceptible to the stabilizing H-or Cl-loss reactions that shut down naphthalene formation. Similarly, our previous results also indicate that Cl-loss at the ring closure site should exhibit appreciably lower dissociation energies than any 37 ). The prediction of 1,2,3,5,7,8-hexachloronaphthalene as the major product is, however, contrary to observation, which suggests that Frenklach-based cyclization channels are only minor contributors at best.…”
Section: ■ Introductionsupporting
confidence: 79%
See 2 more Smart Citations
“…The chlorinated 2-vinylphenyl radicals to which the second acetylene adds are typically found to be higher in energy than the 2-phenylvinyl radicals which serve as the base in Bittner−Howard routes, but far less susceptible to the stabilizing H-or Cl-loss reactions that shut down naphthalene formation. Similarly, our previous results also indicate that Cl-loss at the ring closure site should exhibit appreciably lower dissociation energies than any 37 ). The prediction of 1,2,3,5,7,8-hexachloronaphthalene as the major product is, however, contrary to observation, which suggests that Frenklach-based cyclization channels are only minor contributors at best.…”
Section: ■ Introductionsupporting
confidence: 79%
“…Early studies suggested dissociation barriers of 123.0 kJ mol −1 from C 8 Cl 7 , a downward revision of a mere ∼30 kJ mol −1 from analogous values utilized in nonchlorinated systems. 51,52 However, in part 1 37 we noted a downward revision of ∼70 kJ mol −1 was perhaps more realistic.…”
Section: ■ Conclusionmentioning
confidence: 81%
See 1 more Smart Citation
“…For example, in Kim’s experiment, 2-CP produced mostly 1-MCN and 1,5/1,6/1,7-DCNs; 4-CP produced mostly 2-MCN and 2,6/2,7-DCNs; 3-CP produced nearely equivalent 1-MCN and 2-MCN, and nearly equal 1,5/1,6/1,7-DCNs and 2,6/2,7-DCNs [ 32 , 33 ]. In addition, this hypothesis was, again, denied by some experimental observations in thermal processes that the correlation between PCN and PCDF isomer distributions or mass concentrations is more closer than that between PCN and PCDD, which indicate a new PCN formation mechanism more similar with PCDF formation than PCDD [ 30 , 31 , 42 , 43 , 44 , 45 , 46 ]. In this situation, Kim proposed an alternative PCN formation mechanism based on experimental results [ 32 , 33 , 34 ]; in his scheme, PCNs are formed via carbon-carbon coupling at ortho -sites of CPR pairs, resulting in an intermediate chlorinated o,oʹ-dihydroxybiphenyl (chloro-DOHB) [ 32 , 33 , 34 ].…”
Section: Introductionmentioning
confidence: 99%
“…The most direct route to the formation of PCNs is the gasphase reaction of chemical precursors, including unsubstituted naphthalene [12,13], polycyclic aromatic hydrocarbon (PAHs) [14,15], chlorophenyl radicals [16,17] and chlorophenols (CPs) [6][7][8][9][18][19][20]. Among the variety of precursors, CPs are the most direct precursors of PCNs along with PCDD/Fs and the most common aromatic compounds found in incinerator gas emissions [21][22][23].…”
Section: Introductionmentioning
confidence: 99%